The development and implantation of a biologically derived allograft scaffold. (3rd April 2013) - Nowocin, Anna K.; Southgate, Aaron; Shurey, Sandra; Sibbons, Paul; Gabe, Simon M.; Ansari, Tahera
Abstract: Biologically derived scaffolds are becoming viable treatment options for tissue/organ repair and regeneration. A continuing hurdle is the need for a functional blood supply to and from the implanted scaffold. We have addressed this problem by constructing an acellular ileal scaffold with an attached vascular network suitable for implantation and immediate reperfusion with the host's blood. Using a vascular perfusion approach, a segment of porcine ileum up to 30 cm long, together with its attached vasculature, was decellularized as a single entity. The quality of the decellularized scaffold was assessed histologically and using molecular tools. To establish vascular perfusion potentials of the scaffold, a right‐sided nephrectomy and end‐to‐end anastomosis of the decellularized scaffold's vasculature to a renal artery and vein were performed in a pig of similar size to the donor animal. Lengths of ileal scaffold, together with its attached vasculature, were successfully decellularized, with no evidence of intact cells/nuclear material or collagen degradation. The scaffold's decellularized vascular network demonstrated optimum perfusion at 1, 2 and 24 h post‐implantation and the mesenteric arcade remained patent throughout the assessment. The 1, 2 and 24 h explanted scaffolds demonstrated signs of cellular attachment, with cells positive for CD68 and CD133 on the vascular luminal aspect. It is possible to decellularize clinically relevant lengths of small intestine, together with the associated vasculature, as a single segment. The functional vascular network may represent a route for recellularization for future regeneration of bowel tissue for patients with short bowel syndrome. Copyright © 2013 John Wiley & Sons, Ltd.